Pengaruh Model Permainan Invasi terhadap Teknik Menggiring Bola di Ektrakurikuler Sepakabola SMA Negeri 1 Warungkiara 2017/2018 - Taufan Ramadhan (FKIP Universitas Muhammadiyah Sukabumi, 2018)
This research event will be based the discovery of problem in a field that is oftenthe players SMAN 1 warungkiara experience a failure when the masterball. Therefore,problems arise that are found namely the lack of skills of the dribble. This research aims toknow is there any significant effects from the model the game invasion against the dribbletechniques in SMA Negeri 1 Warungkiara Sukabumi district year 2018.The results showedthat the results of the calculation with a value t calculate â‰¥ t tables i.e. thitung = ttabel = â‰¥7.090 2.1009. So the hypothesis that States there are significant effects from the model thegame invasion against the dribble techniques in SMA Negeri SMA Negeri 1 WarungkiaraSukabumi district year 2018, proved to be the truth.